Acupuncture combined with swallowing training for poststroke dysphagia: a meta-analysis of randomised controlled trials. Issue 2 (April 2019) - Li, Ling Xin; Deng, Kai
Objective: This meta-analysis aimed to assess the efficacy and safety of the combination of acupuncture with swallowing training for poststroke dysphagia. Method: Nine electronic databases (including PubMed and China National Knowledge Infrastructure) were searched from their inception through June 2016. Seventeen studies were included in this meta-analysis. Data on 1479 eligible patients were extracted, and the relative risk (RR) and standard mean difference (SMD) with 95% CI for the effective rate (ER), swallowing function assessment (SFA), individual activity (IA), eg., modified Barthel Index (MBI) and quality of life (QOL) were evaluated. Results: The pooled ER (RR 1.26, 95% CI 1.19 to 1.34, P<0.001, 14 studies) and SFA (SMD 1.06, 95% CI 0.79 to 1.32, P<0.001, five studies) suggested that combination therapy yielded a significantly higher ER and improved the SFA scores to a greater degree than swallowing training alone in patients with poststroke dysphagia. The pooled QOL score (SMD 1.06; 95% CI −0.04 to 2.17, P=0.06, two studies) did not differ between groups. The MBI data (SMD 1.47, 95% CI 1.07 to 1.87, P<0.001, one study) showed significant improvement in IA. Some evidence of publication bias was observed for the ER, although the trim-and-fill analysis and fail-safe number indicated no influence of publication bias on its pooled effect size. There was no evidence of publication bias of any other outcome measures. Conclusion: This study showed that acupuncture combined with swallowing training may improve the ER, swallowing function and activities of daily life of patients with poststroke dysphagia compared with conventional swallowing training alone.